Integrated use of phosphorus fertilizer and farmyard manure improves wheat productivity by improving soil quality and P availability in calcareous soil under subhumid conditions - Jamal, Aftab; Saeed, Muhammad F.; Mihoub, Adil; Hopkins, Bryan G.; Ahmad, Iftikhar; Naeem, Asif (Frontiers in Plant Science, 2023)
Low soil fertility and high fertilizer costs are constraints to wheat production, which may be resolved with integrating fertilizer phosphorus (P) and farm-yard manure (FYM). Study objectives were to evaluate P source impacts on soil, P efficiency, and wheat growth in a calcareous soil. Treatments included P fertilizer (0, 17, 26, or 39 kg P ha-1) and/or FYM (0 or 10 T ha-1) in a: 1) incubation experiment and 2) wheat (Triticum aestivum spp.) field experiment. Soil organic matter increased (30-72%) linearly for both fertilizer and FYM, whereas pH decreased (0.1-0.3 units) with fertilizer only. Addition of fertilizer and FYM increased plant available P (AB-DTPA extractable soil P) an average of 0.5 mg P kg-1 soil week-1 with incubation. The initial increase was 1-9 mg P kg-1, with further increase after 84 d of ~3-17 mg P kg-1. There was also a significant increase of available P in the soil supporting plants in the field study, although the magnitude of the increase was only 2 mg kg-1 at most for the highest fertilizer rate + FYM. Grain (66 to 119%) and straw (25-65%) yield increased significantly, peaking at 26 kg P ha-1 + FYM. The P Absorption Efficiency (PAE), P Balance (PB), and P Uptake (PU) increased linearly with P rate, with the highest levels at the highest P rate. The P Use Efficiency (PUE) was highest at the lowest rates of P, with general decreases with increasing P, although not consistently. Principal component analysis revealed that 94.34 % of the total variance was accounted for with PC1 (84.04 %) and PC2 (10.33 %), with grain straw yield significantly correlated to SOM, PU, and PAE. Regression analysis showed highly significant correlation of PB with P-input (R2= 0.99), plant available P (R2= 0.85), and PU (R2= 0.80). The combination of FYM at the rate of 10 T ha-1 and fertilizer P at 26 kg P2O5 ha-1 was found as the optimum dose that significantly increased yield. It is concluded that FYM concoction with fertilizer-P not only improved SOM and residual soil P, but also enhanced wheat yields with reasonable P efficiency.